Volumetric and Morphometric Analysis of Pineal and Pituitary Glands of an Indian Inedial Subject - Raghuprasad, M.S.; Manivannan, M. (Annals of Neurosciences, 2018)
Background: Inedia (Latin for “fasting”) is the ability of a person to live without consuming food and water and to sustain solely by prana, the vital life force in Hinduism. According to Ayurveda, sunlight is one of the main sources of prana, and some practitioners believe that it is possible for a person to survive on sunlight alone. Purpose: In this study, we report the unusual sizes and volumes of both the pineal and pituitary glands in a subject with inedia state for nearly 70 years. Methods: The pineal and pituitary glands were located in the MRI of the subject from coronal, axial, and sagittal images. Segmentation of the pineal and pituitary glands was performed using level set active contours method. Results: The overall volume, size, and shape of the glands were calculated as 38.7604 mm 3 for the pineal gland and 272.552 mm 3 for the pituitary gland and compared with that of the normal volumes (94.2 ± 40.65 mm 3 and 320–718 mm 3 , respectively). Conclusion: It was found that the subject has significantly low pineal and pituitary volumes, which fall under the category of normal young child and we could show that the neurohormonal morphology of inedia subject is within childhood range.